Comparison of tympanoplasty results with use of perichondrium- cartilage and temporalis facia - Seyed Basir Hashemi; Habib Sohrabi; Hajar Bohranifard (Iranian Journal of Otorhinolaryngology, 2009)
Introduction: The use of cartilage in reconstruction of the tympanic membrane has been established especially in cases such as tubal dysfunction and adhesive processes. Cartilage offers the advantage of higher mechanical stability compared with membranous materials but may alter the acoustic transfer characteristics of the graft. The purpose of this study was to investigate the hearing results after thin cartilage – perichondrium tympanoplasty, versus temporalis facia tympanoplasty. Materials and Methods: In this clinical trial, tympanic membrane reconstruction was operated with thin perichondrium-cartilage slices in one group of patients and temporalis facia in another group. Post operation Speech reception threshold (SRT) and graft take rate were compared statistically between two groups. Results: After one-year follow up, the graft take rate was 98% in the temporalis fascia group and 96.8% in the cartilage perichondrium group. The mean improvement of SRT was 17.9db for cartilage-perichondrium group and 21.6db for temporalis fascia group. The difference was not statistically significant. Conclusion: Considering the results of this study, cartilage-perichondrium tympanoplasty offers the possibility of a rigorous tympanic membrane (TM) reconstruction with no statistically significant differences in post operative hearing results.